X-Linked Lymphoproliferative Disease Presenting as Pancytopenia in a 10-Month-Old Boy - S. Nicole Chadha; David Amrol (Case Reports in Medicine)
X-linked lymphoproliferative disease, also known as Duncan's syndrome, is a rare genetic disorder that causes exaggerated immune responses to Epstein-Barr virus (EBV) infection and often leads to death. Patient presentation varies but can include signs and symptoms typical of EBV, pancytopenia, and fulminant hepatitis.